MODERN DISTANCE EDUCATION IN UZBEKISTAN AND ITS DEVELOPMENT PROSPECTS (Ta'limning zamonaviy transformatsiyasi, 2024)
The article considers distance education that requires rethinking and modernization of existing methods of teaching the educational process that have developed in the contact-classroom environment. Opportunities, advantages and disadvantages of online education, and prospects for applying joint traditional and distance education.